2021
DOI: 10.1111/jora.12670
|View full text |Cite
|
Sign up to set email alerts
|

Sleepy and Secluded: Sleep Disturbances are Associated With Connectedness in Early Adolescent Social Networks

Abstract: Studies in adults suggest that sleep disturbances predict poorer socioemotional skills and impaired social interactions. However, little is known regarding how sleep problems are associated with social processes during adolescence, a period when both sleep neurobiology and social relationships are undergoing dramatic developmental changes. The current study examined associations among sleep disturbances and peer connectedness among a sample of middle-school students (N = 213, 11-15 years old, 57% female) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Studies across school-aged and adolescent samples demonstrate that CDS symptoms are a strong correlate and predictor of depressive symptoms (Becker, Willcutt et al, 2022; Fredrick, Langberg et al, 2022). CDS symptoms may be associated with elevated depressive symptoms due to overlapping hypoactive behaviors (e.g., lethargy and daytime sleepiness) (Fredrick, Yeaman et al, 2022) or greater active peer rejection (Fredrick, Langberg et al, 2022), which, in turn, may result in withdrawing oneself from the peer group as a result of less motivation or self-regulatory deficits (Palmer et al, 2022). Due to overlapping temperamental and external correlates, such as BI, shyness, and internalizing symptoms, researchers have speculated that CDS may be uniquely and strongly linked to symptoms of social anxiety (Becker et al, 2019).…”
Section: Mechanisms Linking Cds To Social Withdrawalmentioning
confidence: 99%
“…Studies across school-aged and adolescent samples demonstrate that CDS symptoms are a strong correlate and predictor of depressive symptoms (Becker, Willcutt et al, 2022; Fredrick, Langberg et al, 2022). CDS symptoms may be associated with elevated depressive symptoms due to overlapping hypoactive behaviors (e.g., lethargy and daytime sleepiness) (Fredrick, Yeaman et al, 2022) or greater active peer rejection (Fredrick, Langberg et al, 2022), which, in turn, may result in withdrawing oneself from the peer group as a result of less motivation or self-regulatory deficits (Palmer et al, 2022). Due to overlapping temperamental and external correlates, such as BI, shyness, and internalizing symptoms, researchers have speculated that CDS may be uniquely and strongly linked to symptoms of social anxiety (Becker et al, 2019).…”
Section: Mechanisms Linking Cds To Social Withdrawalmentioning
confidence: 99%
“…Social network analysis literature on health behaviors has largely focused on personal health behavior similarity with members of one's social network and popularity analysis based on practiced health behaviors and has covered a limited selection of such behaviors, including smoking, drinking, and eating (Montgomery et al, 2020). From the aforementioned literature, it is known that young people in more established networks usually exhibit less unhealthy behaviors than those who have smaller networks (Montgomery et al, 2020;Palmer et al, 2022). Young people, including the vulnerable, report better health if they have more network resources, and health conditions may predict the number of social ties (Nevard et al, 2021;Hu and Cai, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for links between social isolation and sleep difficulties is most robust in studies of adults. However, several recent studies have revealed associations between social isolation and sleep difficulties during adolescence [ 26 , 29 ]. At any age, social isolation may act as an interpersonal stressor that promotes rumination and interferes with sleep.…”
Section: Introductionmentioning
confidence: 99%